Glargine safety, diabetes and cancer. (March 2013) - Rendell, Marc; Akturk, Halis Kaan; Tella, Sri Harsha
<x xml:space="preserve">Abstract</x> Introduction: In 2009, several epidemiological studies suggested a higher frequency of malignancy in <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=insulin glargine&logicalOpe1=OR&field2=articletitle&text2=insulin glargine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">insulin glargine-treated patients. A number of follow-up epidemiological population studies as well as two randomized, controlled clinical studies, one a 5000-patient retinopathy study and the other a 12, 000-patient cardiovascular outcomes trial (ORIGIN), found no higher frequency of malignancy in glargine-treated patients. Areas covered: We reviewed the existing literature as well as U.S. FDA records to investigate the association of cancer, diabetes, and insulin. There is a 20 – 40% higher incidence of malignancy in type 2 diabetes patients. Certain cancers are more common, including hepatocellular and pancreatic carcinoma, colorectal cancer, renal cancer, and breast and endometrial cancer, and non-Hodgkin's lymphoma. There are numerous inter-related factors which may promote both diabetes and malignancy, including dietary patterns, obesity, insulin resistance, and alcoholism. Patients who receive insulin treatment are typically older and "sicker" than those who receive oral agents. Expert opinion: It is very difficult to prove causal associations between diabetes and cancer due to the host of confounding factors. The hypothesis that hyperinsulinemia and IGF-1 receptor activation promote cancer is strong, but confounded by the association of hyperinsulinemia with obesity, which separately promotes malignancy. Although statistical techniques to adjust for confounding variables can improve epidemiological comparisons, the lesson of the glargine cancer controversy is that controlled clinical trials are the only means to definitely prove hypotheses.